Undergraduate Engineering Student’s System Thinking of Their Teaching and Learning about Indian Accreditation: Enhancing Undergraduate Engineering Education in India through Systems Thinking (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Engineering faculties across India are experiencing substantial pressure from industry, the professional body and their own institutions to contextualise and embed generic graduate attributes in undergraduate programs. Responding to this pressure is proving challenging in India with three inter-related problems evident in the Indian engineering education literature Innovative teaching and learning of graduate attributes tends to be isolated and short-lived rigorous evaluation of impact on student learning is rare and contextualization of institutional graduate attributes statements tends to be limited. In India and internationally, greater discourse, research and development are needed to embed engineering design-relevant meta-attributes (eg. reflective practice, creativity, social justice, systems thinking) in undergraduate engineering. The focus of this paper and our research is the teaching, learning and assessment of the meta-attribute systems thinking.